Aleister Crowley and Western esotericism / edited and introduced by Henrik Bogdan and Martin P. Starr ; foreword by Wouter J. Hanegraaff. - Bogdan, Henrik; Bogdan, Henrik; Starr, Martin P., 1959-; Starr, Martin P., 1959- (Oxford University Press, 2012)
This volume is the first comprehensive examination of one of the twentieth century's most distinctive iconoclasts. Aleister Crowley (1875-1947) was a study in contradictions. Born into a fundamentalist Christian family and educated at Cambridge, he was vilified as a traitor, drug addict, and debaucher, yet revered as perhaps the most influential thinker in contemporary esotericism. Moving beyond the influence of contemporary psychology and the modernist understanding of the occult, Crowley declared himself the revelator of a new age of individualism. Crowley's occult bricolage, Magick, was an eclectic combination of spiritual exercises drawn from Western European magical ceremonies and Indic sources for meditation and yoga. This journey of self-liberation culminated in harnessing sexual power as a magical discipline, a "sacrilization of the self" as practiced in Crowley's mixed masonic group, the Ordo Templi Orientis. The religion Crowley created, Thelema, legitimated his role as a charismatic revelator and herald of a new age of freedom. Aleister Crowley's lasting influence can be seen in the counter-culture movement of the late 1960s and early 1970s and in many forms of alternative spirituality and popular culture. The essays in this volume offer crucial insight into Crowley's foundational role in the study of Western esotericism, new religious movements, and sexuality